CEREBROVASCULAR DISORDERS IN PATIENTS WITH COVID-19 CONSEQUENCES PATHOGENETICALLY DETERMINED DIAGNOSIS AND METHODS OF CORRECTION - Stoyanov, O.M.; Kalashnikov, V.Y.; Vastyanov, R.S.; Mirdzhuraev, E.M.; Son, A.S.; Fedorenko, T.V.; Ostapenko, I.O. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate and to correct the state of the autonomic system, cognitive functions, vestibular apparatus and cerebral blood circulation autoregulation in patients with cerebrovascular pathology formed as the result of COVID-19 consequences. Patients with chronic cerebral inschemia in the compensated and subcompensated stages together with 46 patients with ischemic stroke were examined. The Mini-Mental State Examination and Frontal Assessment Batter ctiteria were used together with 10-word recall test. Vegetative characteristics were investigated in patients: tone, reactivity and vegetative activity ensuring, together with brain arteries reactivity in triplex mode using an ultrasound scanner. Cognitive, psychoemotional, vestibular, and autonomic disorders have been found to be key and comorbidities of cerebrovascular insufficiency in people who have experienced COVID-19 and are correlated with the degree of brain damage. Their progression is facilitated by the transferred coronavirus infection with subsequent decompensation of ischemia, especially as a result of direct damage to the CNS vascular system. The use of β-phenyl-GABA restores cognitive functions, affects vestibular structures, improves their vascularization, has a harmonizing vegetotropic, antidepressant effect, and also normalizes cerebrovascular reactivity.
Keywords: cerebrovascular pathology; coronavirus infection; vegetative system; cognitive and vestibular disorders; nervous system damage; β-phenyl-GABA